Residential Landscaping Methods in Planning Structure of the Residential Area - N. V. Drobchenko; G. N. Dzhuraeva (Researchparks Publishing, 2021)
The article discusses the techniques of landscaping a residential area, the principle of a stepwise system of servicing residential complexes is considered, examples of the assortment of vegetation for these territories are given.